Konsep Hukum Islam Tentang Jual Beli Mata Uang (Al-Sharf) - Nuramirah; Syamsurijal (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2022)
International trade activities always require the transfer and conversion of currencies from one country to another. This is because every independent country in the world has the authority to determine the currency used and the exchange rate (the exchange rate of a country's currency with other countries). The purpose of this research is to analyze Islamic law regarding currency trading. The results of the study can be concluded that the legal concept in the implementation of the sharf in Indonesia is regulated through the Fatwa of the National Syari'ah Council of the Indonesian Ulema Council No: 28/DSN-MUI/III/2002 concerning the Sale and Purchase of Currency (Al-Sharf) which in general terms explain that currency buying and selling transactions are allowed in principle.